1865 Fla. Laws 25 - (:unkn) unknown (My University, 1865)
Ch. 1466, § 12: Prohibited "any negro, mulatto, or other person of color" to keep or bear Bowie-knives, dirks, swords, fire-arms, or ammunition of any kind without a license from the Judge of Probate in their county of residence. Violators subject to confiscation of weapons, including a sentence of one hour in the pillory, or be whipped, not exceeding thirty-nine "stripes."
Keywords: ENSLAVED PERSONS & OTHER MINORITIES